Pengaruh Pemberian Buah Sawit Terhadap Pertambahan Bobot Badan, Konsumsi Dan Konversi Pakan Ayam Kampung - Suharto, Beri; Ali Akbar, Syahro; Sari, Rica Mega; Astuti, Tri (Program Studi peternakan, 2023)
This research aimed to determine the effect of using palm fruit on body weight gain, feed consumption, and feed conversion of free-range chickens. It is hoped that the results of this research will provide information for breeders, especially about the benefits of using palm fruit in free-range chicken feed. This research used a Completely Randomized Design (CRD) with 4 (four) treatments and 5 (five) replications. In the research done with 60 head native chickens 1 (one) month ages. The research results showed that the increase in body weight of native chickens in the P0 treatment = 15.23 grams; P1 = 11.43 grams; P2 = 14.59 grams; and P3 = 14.14 grams. Feed consumption in treatment P0 = 81.44 grams; P1 = 63.85 grams; P2 = 62.86 grams; and P3 = 62.71 grams. Feed conversion in treatment P0 = 5.80; P1 = 5.96; P2 = 4.47; and P3 = 4.65. The research results can be concluded that the use of 50 % palm fruit (P2) native chicken feed produces relatively the same body weight gain as the control treatment (P0), relatively efficient feed consumption compared to other treatments, and relatively the same feed conversion as using 25% palm fruit ( P3).